The secrets of spies - Vescent, Heather; Gilbert, Adrian; Colson, Rob 1971- (Weldon Owen, 2020)
From James Bond to Mata Hari, in scores of books and movies, and on the front pages of newspapers, spies have always captured our imagination. But what's the truth behind the fiction? The Secrets of Spies sheds light on the mysterious life of the spy, explaining the real-life origins of spying, examining some of history's most notorious spies and spycatchers, and revealing the role espionage plays today in business, politics, and everyday life. Filled with lavish illustrations and hundreds of full-color photographs, this book provides hours of fun and entertainment for any reader. Narrated in an engaging, compelling style, The Secrets of Spies is a thrilling, in-depth global investigation of the hidden history of espionage. From ninja assassins to computer hackers, the book uncovers the tools, tricks, and techniques that make up the daring art of the spy.